MAKNA DAN NILAI BUDAYA YANG TERKANDUNG DALAM LAGU-LAGU DAERAH EVAV DI MALUKU TENGGARA KAJIAN ANTROPOLOGY SASTRA - Renyaan, Petronela; Muzrifah, Risa Amalia; Herawati, Fitri (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2020)
Literary works are imaginative works that use the language of literature. The language used is different from everyday life because the ambiguous nature and expression of this causes the language of literature tends to influence, make and eventually change the attitude of the reader. The problems to be discussed in this study are (1) describing and classifying lingual unit forms of cultural terms contained in kei song lyrics, (2) describing and classifying the meanings of cultural terms contained in Kei song lyrics. This research has benefits, namely theoretical and practical. The method used in this research has a qualitative method used because the data obtained in the form of sentences are not numbers. Data and data sources are derived from lyrics of kei songs, data collection techniques use listening techniques, note techniques, data analysis techniques using dressing techniques. and the value of the song evav. The mandate contained in the lyrics of evav songs in terms of overall, how to just be humble to parents and humble days to anyone and always remember themselves wherever and whenever.